High‐Strength, Thermally Stable, and Processable Wood Fiber/Polyamide Composites for Engineering Structural Components - Zhengtong You; Haigang Wang; Feng Zhang; Haoyuan Zhang; Chuwen Zou; Zhifang Zhou; Yonggui Wang; Zefang Xiao; Daxin Liang; Qingwen Wang; Wentao Gan; Yanjun Xie (Advanced Science)
Abstract Hybrid wood fiber/plastic composites offer a high‐value‐added utilization for agroforestry waste, which also providing a promising solution for reducing white pollution. However, the interface incompatibility between natural wood fibers and polymers significantly impairs the mechanical properties of the composites. Herein, a straightforward procedure is proposed to solve this problem, involving the removal of low‐thermal‐stability hemicellulose from wood fibers by hydrothermal pretreatment, followed by compositing with polyamide to produce hydrothermally treated wood fiber/polyamide composites (HWPACs). No chemical additives are required to improve the interface compatibility of composites, which simplifies the manufacturing process and provides environmental benefits. The effective removal of hemicellulose (78.35%) significantly increases the onset thermal degradation temperature of hydrothermally treated wood fibers (HWFs) by 27.49 °C. This prevents the generation of micro gaps during thermal processing, thereby improving the interfacial bonding strength between HWFs and polyamide. HWPACs exhibit higher mechanical strength (flexural strength 139.45 MPa) and thermal stability while maintaining a low density (1.22 g cm−3). Various lightweight, high‐strength, and multi‐shape materials can be prepared by hot pressing, injecting, and printing HWPACs, suggesting their suitability for applications in engineering structural components.